Job stress in relation to job performance: a case study - Erika Dolores Ruiz; Julio Fernando Salazar Gómez; María de Jesús Valdivia Rivera; Manuel Hernández Cárdenas; Ibis Rafael Huerta Mora (RAN, 2023)
Purpose: To analyze the relationship between occupational stress and job performance in the workers of a business group in the Tierra Blanca region, Veracruz, Mexico. Design/methodology: To determine the relationship between the variables work stress and work performance using a linear regression model and to determine the level of significance among variables by analyzing the variance. Results: There is a positive correlation between the variables work stress and work performance, as well as a positive linear significance. Implications: This study findings will allow MSMEs to adopt strategies to benefit their workers. Originality: The study is aimed at MSMEs. These studies findings are often relevant to large organizations. However, the MSMEs, which also manage human capital, can also implement improvements for the wellbeing of their workers based on these results.